Constitutional Requirements regarding the Restriction of the Exercise of Fundamental Rights during the Pandemic - Nita, Anca-Jeanina (Acta Universitatis Danubius. Administratio, 2022)
Following the official recognition, by the World Health Organization (W.H.O.) of the COVID-19 pandemic, nation states have adopted specific measures to prevent infections and combat the pandemic The governments of a large number of states have reacted to the pandemic as a matter of national security; some member countries of the Council of Europe - including Romania have resorted to the right of derogation stipulated by the art. 15 of the European Convention on Human Rights.